If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(q + 2) = q + 1 Reorder the terms: 2(2 + q) = q + 1 (2 * 2 + q * 2) = q + 1 (4 + 2q) = q + 1 Reorder the terms: 4 + 2q = 1 + q Solving 4 + 2q = 1 + q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-1q' to each side of the equation. 4 + 2q + -1q = 1 + q + -1q Combine like terms: 2q + -1q = 1q 4 + 1q = 1 + q + -1q Combine like terms: q + -1q = 0 4 + 1q = 1 + 0 4 + 1q = 1 Add '-4' to each side of the equation. 4 + -4 + 1q = 1 + -4 Combine like terms: 4 + -4 = 0 0 + 1q = 1 + -4 1q = 1 + -4 Combine like terms: 1 + -4 = -3 1q = -3 Divide each side by '1'. q = -3 Simplifying q = -3
| 3x-14=-8x-36 | | 5+5r-2=9r+11-3r | | log(4)+log(x-1)=log(3x) | | 3x+2y-4x+3= | | (9+7i)(8-3i)= | | 8z+5=1 | | 2y+5x=77 | | 4x+7-x=13 | | -7x-10=-136 | | 12x-3x^2=12 | | 9(t-3)+3t=6(2t+4)-12 | | a+2a+3a=12 | | -12(x-1)=4(x+9) | | 4x^2-16x-208=0 | | 8x+4y+6u+2z=-16 | | x^3-x^2-3x-1=0 | | 29-11=30-x | | 95-63=x-60 | | 8x-7=-10+9x | | 8x-4x-20=4 | | 89-45=90-x | | 2(2a+2)=11+3a | | 37-21=x-24 | | x-a+2=2ax-3x | | 7z-11=43+z | | a^2+11a=12 | | ln(2x+-9)=0 | | 3s^2+28x-3=0 | | F(x)=x^2-15x+15 | | 43-26=40-x | | 5.2x=31 | | 17x+12=17x-12 |